Unconventional Warfare from Antiquity to the Present Day
IX, 264 p. 6 illus.
Keywords: This volume addresses the problem of small, irregular, and unconventional war across time and around the globe. The use of non-uniformed and often civilian combatants, with tactics eschewing pitched battles, is the most common form of warfare throughout history and comes in many forms. The collection works back in time beginning with the ‘Long War’ in present day Afghanistan and concluding with warfare in classical Greece. Along the way it engages with conflicts as diverse as the American Civil War and regional rebellion in Tudor England. Each case study provides unique insights into the practices, experiences, and discourses that have shaped this ubiquitous type of conflict. Readers interested in rebellion and repression, cultural and tactical interpretations of conflict, civilian strategies in wartime, the supposed ‘western way of war’, and the ways in which participants have framed and related their actions across a variety of spheres will find much of interest in these pages.